2020
DOI: 10.7888/juoeh.42.237
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Density Assessment and Characterization of Water and Sanitation Facilities in the Informal Settlements of Kisumu City: Implications for Public Health Planning

Abstract: Access to water and sanitation remain a challenge in many developing countries, especially in pro-poor urban informal settlements where socioeconomic livelihoods are generally low. The aim of this study was to characterise the water and sanitation facilities in the informal settlements of Kisumu City and to evaluate their effect on community hygiene and health. The study focussed on the five urban informal settlements of Nyalenda A, Nyalenda B, Manyatta A, Manyatta B and Obunga, and the three Peri-urban inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Specifically, as in many previous studies [ 31 , 40 , 43 , 44 , 45 , 46 ], we found that wealth is an essential factor in access to a safe drinking water source in informal settlements. Although the SES in informal settlements is generally low [ 28 ], the use of a piped tap on the property is still disproportionately concentrated among households with higher SES (positive concentration index). To diminish these inequalities and ensure consistent and quality access to drinking water for all, investment in piped drinking water is needed [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, as in many previous studies [ 31 , 40 , 43 , 44 , 45 , 46 ], we found that wealth is an essential factor in access to a safe drinking water source in informal settlements. Although the SES in informal settlements is generally low [ 28 ], the use of a piped tap on the property is still disproportionately concentrated among households with higher SES (positive concentration index). To diminish these inequalities and ensure consistent and quality access to drinking water for all, investment in piped drinking water is needed [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these water resources might be polluted due to industrial and household waste, making them potentially unsafe for humans [ 8 , 23 ]. Pollution could be the result of broken septic tanks, irrigation, and run-off water containing agrochemicals, which could spread infectious diseases, including cholera and typhoid [ 28 ]. Thus, the lack of access to piped tap water might result in poor health outcomes and the spread of diseases due to the use of contaminated water sources [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is known accelerate contamination of groundwater and in effect spread of antibiotic resistance due to the rise in the number of on-site sanitation facilities like pit latrines [31]. There is likely interaction of the aquifer and sanitation facilities due to the limited construction depth of both pit latrines and shallow wells in the study site [29,39]. The Kisumu drainage network and the wastewater treatment site are close to the sites where antibiotic resistant E. coli were isolated, indicating a possible contamination in the sub-surface.…”
Section: Plos Watermentioning
confidence: 99%